Application Creative Problem Solving to Improve Junior High School Students' Creative Thinking Skills in Environmental Pollution Materials - Izzatina, Sabila; Rosdiana, Laily (Science Education and Application Journal, 2024)
Education is an effort to improve the quality of life and human resources. One of these educational goals is to increase student creativity in learning at school. The purpose of this study was to determine the increase in students' creative thinking skills, learning implementation, and the responses of class VII E students of SMP Negeri 2 Semen after implementing the learning process by applying the creative problem solving learning model to environmental pollution material. The research method used is Pre-Experimental Design with the experimental design used is One-Group-Pretest-Posttest. The research subjects in this study were students of class VII E with a total of 34 students at SMP Negeri 2 Semen Kediri. Data collection using tests (pretest-posttest), observation sheets of learning implementation, and student response questionnaires. Based on the results of the study after carrying out learning by applying creative problem solving it was found that students' creative thinking skills increased with an N-Gain value of 0.75 with very high criteria. The application of the creative problem solving learning model in class VII E of SMP Negeri 2 Semen was carried out well, this can be seen from the mode value of the results of observing the implementation of learning, namely 4. Student responses to the application of creative problem solving learning models in environmental pollution material received a value of 85, 10% with very high criteria which means students give a positive response. The conclusion from this study is that the creative problem solving learning model influences the creative thinking skills of class VII E students of SMP Negeri 2 Semen Kediri.